Practitioner Action Research for Studying Higher Education and Improving the Quality of Teaching - Tony Harland (UUM Press, 2010)
There is increasing interest in the quality of university teaching and how academics learn to be teachers. This paper examines the idea of empowering academics as researchers of their own teaching practices so they not only learn about that practice, but also make a commitment to knowledge for the wider teaching community and contribute to the theories of higher education. The arguments draw on the historical context of influences on professional learning and what can be understood from the changing conceptions of working practices in our universities. The paper concludes with some reflections on the current Malaysian situation where the idea of practitioner research for university lecturers is currently being explored.